If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (-3) = 100 x + -3 = 100 Reorder the terms: -3 + x = 100 Solving -3 + x = 100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 100 + 3 Combine like terms: -3 + 3 = 0 0 + x = 100 + 3 x = 100 + 3 Combine like terms: 100 + 3 = 103 x = 103 Simplifying x = 103
| 5x=9x+20 | | 4x^2+16x-28=0 | | -x^2+7-10=0 | | 3+d3–d | | -3x=23 | | 113-2x=16x+17 | | -(1+7k)-8k=7-7k | | 125d+12=3500 | | 9t^3-64t=0 | | (2x-3)2= | | 2(4a-12)+3a=6a | | 3r+7=16 | | 4/3=x | | 8X=13Y | | -3(x+2)-1=2(x-5)-5x | | 12-10x=102-45x | | 3+(4*8)56= | | 3x-1=32 | | 4c-3=25 | | x+(1.5x)=45000 | | 49=-6c+9+2c | | 8(2n-2)=2(8n-8) | | 3y^2-5y+8=0 | | .50*-3= | | 3y^2-5y=8 | | 3/4(4x-8)=2/3(6x+15) | | 4(x+2)/4=26 | | -8(x+6)+4=-44 | | 4c-3=35 | | 3(x-5)/2=18 | | x+4=3x-5 | | 7m-8m+2=3 |